2012
DOI: 10.2166/wst.2012.224
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Zn and Cu unit output loads from animal husbandry facilities

Abstract: Zinc (Zn) and copper (Cu) are toxic to aquatic organisms at very low concentrations that do not affect humans. We measured the daily output of Zn and Cu in wastewater from livestock farms to aquatic environments because waste from animal husbandry operations contains high levels of Zn and Cu. At most pig farms in Japan, a mixture of urine, some faeces, and service water is treated in onsite wastewater treatment facilities and discharged into a water body. Some dairy farms also have wastewater treatment facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…We found that the concentration of Zn in the swine farm effluent at P5 exceeded both the ES (2.0 mg L -1 ) and the maximum effluent concentration from the WWTF (4.4 mg L -1 ; Abe et al 2012). We consider this high concentration to be undesirable but nevertheless probable based on the following supportive information.…”
Section: Identifying the Dominant Source Of Zn In The Watershedmentioning
confidence: 82%
See 4 more Smart Citations
“…We found that the concentration of Zn in the swine farm effluent at P5 exceeded both the ES (2.0 mg L -1 ) and the maximum effluent concentration from the WWTF (4.4 mg L -1 ; Abe et al 2012). We consider this high concentration to be undesirable but nevertheless probable based on the following supportive information.…”
Section: Identifying the Dominant Source Of Zn In The Watershedmentioning
confidence: 82%
“…The test scenario assumed the Zn concentration in effluent water to be controlled by the criteria for the maximum and average concentrations of Zn in effluent waters: 4400 and 470 μg-Zn L -1 , respectively ( Fig. 3; Abe et al 2012). We assumed that the effluent discharge remained the same.…”
Section: Scenario Analysis For Risk Managementmentioning
confidence: 99%
See 3 more Smart Citations